Positive Periodic Solutions for First-Order Nonlinear Neutral Differential Equations (Journal of Nonlinear Modeling and Analysis, 2025)
We consider a first-order nonlinear neutral differential equation.By employing Krasnoselskii’s fixed point theorem, we provide several newcriteria for the existence of positive periodic solutions to this equation. Thetheorems we have formulated are exemplified through a specific example.
Keywords: Fixed point; neutral equations; positive periodic solution; first-order